ABDULLA AVLONIY ASARLARIDA SO’ZLASHUV TILIGA XOS LUG’AVIY BIRLIKLARNING USLUBIY QO’LLANISHI - Murodova Salomat (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This paper makes analyses of the Abdulla Avloniy scientific works. On this case, identical lexical and dictionary points with specific methods were used to get more points for the further research work. In conclusion, it has views of the different analyses while pointed both outcomes and shortcoming of the Abdulla Avloniy’s scientific works.